Impact of affluence on the local spread of SARS-CoV2 during the first wave of the COVID-19 pandemic - B.R.H. Sturrock; E.I. Chevassut; A. Shahvisi; T.J.T. Chevassut (Elsevier, 2021)
Objectives: Socioeconomic factors such as elevated incidence of chronic disease, overcrowding, and increased occupational exposure result in higher risk of infectious disease. The COVID-19 pandemic has appeared to disproportionately affect communities affected by deprivation and discrimination, who also appear to be at greater risk of severe disease. Our aim was to investigate the evolution of the socioeconomic groups affected by COVID-19 over the course of the first wave of the pandemic by examining patients presenting to an acute NHS trust. Study design: and methods: A retrospective study using the postcodes of patients presenting to the Brighton and Sussex University Hospitals NHS Trust who tested PCR-positive for COVID-19 were used to determine average house price and index of multiple deprivation. These were used as markers of affluence to examine the trend in the socioeconomic status of affected patients from February to May 2020. Results: 384 cases were included. The postcodes of those individuals who were initially infected had higher average house prices and index of multiple deprivation, both of which followed downward trends as the outbreak progressed. Conclusion: Our data shows that the outbreak spread from higher to lower affluence groups through the course of the pandemic. We hypothesise that this was due to wealthier individuals initially transmitting the virus from abroad. Therefore, an earlier and more effective quarantine could have reduced spread to members of the community at greater risk of infection and harm. We suggest that hospitals systematically record the socioeconomic status of affected individuals in order to monitor trends, identify those who may be at risk of severe disease, and to push for more equitable public health policy.